Allometrically Scaled Children's Clinical and Free-Living Ambulatory Behavior. Issue 12 (December 2016) - LIM, JONGIL; SCHUNA, JOHN M.; BUSA, MICHAEL A.; UMBERGER, BRIAN R.; KATZMARZYK, PETER T.; VAN EMMERIK, RICHARD E. A.; TUDOR-LOCKE, CATRINE
ABSTRACT: Purpose: This study aimed to compare clinical and free-living walking cadence in school-age children and to examine how the allometric scaling of leg length variability affects objective ambulatory activity assessment. Methods: A total of 375 children (154 boys and 221 girls, 9–11 yr old) completed GAITRite-determined slow, normal, and fast walks and wore accelerometers for 1 wk. Dependent variables from clinical assessment included gait speed, cadence, and step length, whereas steps per day, peak 1-min cadence, and peak 60-min cadence were assessed during free living. Analogous allometrically scaled variables were used to account for leg length differences. Free-living times above clinically determined individualized slow, normal, and fast cadence values were calculated. Differences in dependent variables between sex and sex-specific leg length tertiles were assessed. Results: Clinically assessed cadence (mean ± SD) was 90.9 ± 15.2 (slow), 113.8 ± 12.9 (normal), and 148.9 ± 20.9 (fast) steps per minute, respectively. During free living, participants accumulated 8651 ± 2259 steps per day. Peak 1-min cadence was 113.4 ± 12.4 steps per minute and peak 60-min cadence was 60.1 ± 11.4 steps per minute. Allometrically scaling gait variables to leg length eliminated the previously significant leg length effect observed in both clinical and free-living gait variables but did not affect the observation that girls exhibited lower levels of free-living ambulatory behavior measured by mean steps per day. On average, all groups spent <15 min·d −1 above clinically determined slow cadence; this was unaffected by leg length. Conclusion: Allometrically scaling gait variables to leg length significantly affected the assessment of ambulatory behavior, such that different leg length groups appear to walk in a dynamically similar manner. Leg length effects on free-living ambulatory behavior were also eliminated by implementing estimates of time spent above individualized cadence cut points derived from clinical gait assessment.